Defoliation triggered by climate induced effects in Spanish ICP Forests monitoring plots - de la Cruz, Ana C.; Gil, Paula M.; Fernández-Cancio, Ángel; Minaya, Mayte; Navarro-Cerrillo, Rafael M.; Sánchez-salguero, Raúl; Grau, José Manuel; De, Ana C.; Gil, Paula M.; Fernández-Cancio, Ángel; Minaya, Mayte; Navarro-Cerrillo, Rafael M.; et al. (Forest Ecology and Management, 2014)
In a context of global change, climate impacts can trigger defoliation processes in different forest species. The ICP Forests network estimates the level of forest defoliation over time in different European countries. Those data are used to related defoliation with potential causal factors. In European Southwestern forests, climate change appears to be the detonating factor of generalized defoliation. The objectives of this study were: (i) identity defoliation trends in forest trees at network of Spanish ICP Forests monitoring plots and, (ii) find out if there are underlying climate factors that trigger defoliation process along the time. The spatiotemporal synchronization of the defoliation response was analyzed with cross-correlation using COFECHA software. The relationship between the 88 climatic variables proposed and defoliation was analyzed using Correlated Component Regression models (CCR models) and Discriminant Analysis (DA). The significance of the variables in each model was compared using contingency tables. A peak of defoliation was observed in the mid-1990s with no recovered to the initial values of the early 1990s. The behavior of the different tree species with respect to defoliation, synchronized both in time and space, involves one or several factors that have a general and similar effect on forests in Spain. The most significant factors related to defoliation were the thermal-related factors, particularly average temperatures in April and June and the thermal oscillation of both the current year and the previous year. Only one drought indicator as statistically significant was identified (A, duration of aridity in months) and suggests that it is of limited relevance in the Spanish forest defoliation conditions.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: climate change; Cross-correlation; crown condition; Forest decline; Mediterranean forests; Synchronization

Artificial regeneration with Quercus ilex L. and Quercus suber L. by direct seeding and planting in southern Spain - González-Rodríguez, Victoria; Navarro-Cerrillo, Rafael M.; Villar, Rafael (Annals of Forest Science, 2011)
& Introduction The limited ability of Quercus species to regenerate naturally in Mediterranean forests has led to the development of various artificial regeneration methods; however, there is no general consensus as to what specific method is the best one for this purpose. & Material and methods In this work, we assessed morphology, growth and survival of two Quercus species (Quercus ilex ssp. ballota and Quercus suber) using two different methods of artificial regeneration (viz. direct seeding and planting) and two seedling ages (1-year-old seedlings and 3-year-old seedlings) in southern Spain. & Results and discussion The 1-year-old seedlings of both species were found to exhibit the highest survival percentages and direct-seeded plants intermediate survival values. For direct-seeded plants, seed mass was found to have a significantly positive effect on the establishment success in both species. No clear-cut trend in survival was detected in the 3- year-old seedlings. The survival of the 3-year-old Q. suber seedlings and the direct-seeded plants was similar, but not in Q. ilex, where the survival of the 3-year-old seedlings was the lowest. The latter result may have been a consequence of cultivation in smaller containers leading to root deformation and limiting plant access to water. Differences in survival could not be ascribed to morphological and growth variables or stomatal conductance. & Conclusion Based on the results, all three artificial regeneration methods can be similarly effective provided appropriate nursery cultivation conditions are used and seeds are protected against predators, the best choice in each case being dictated by the particular restoration goals.
Keywords: artificial regeneration; Nursery; oak; Seedling; sowing